Potential of rice (Oryza sativa L.) cultivars to mitigate methane emissions from irrigated systems in Latin America and the Caribbean - Soremi, Paul Abayomi Sobowale; Chirinda, Ngonidzashe; Graterol Matute, Eduardo Jose; Álvarez, María Fernanda (Informa UK Limited, 2023)
In irrigated rice fields, plant-mediated transfer of CH4 from submerged soils to the atmosphere raise the possibility of genotypic differences in CH4 emissions. Previous research has been contradictory, and varietal differences in rice CH4 emissions in Latin America have not been examined. A field experiment in Colombia tested whether irrigated rice emissions might be reduced using a breeding line, an inbred variety, and two rice hybrids. Data was collected on CH4 emissions, phenotypic, root, and grain yield parameters. Variations observed in CH4 emissions, grain yield, root length, and root surface area were in the order Hybrid 2 > Hybrid 1 > breeding line > inbred variety. CH4 emissions per unit area were between 29% and 62% greater for the hybrids than the inbred variety and breeding line, and CH4 emissions per unit grain yield were comparable across genotypes. Our findings suggest that differences in root characteristics and aboveground biomass explain genetic influences on CH4 emissions. The transition to low-emission rice production systems can be accelerated by using differences in productivity and root qualities among cultivars.